REFORM OF ECONOMIC MANAGEMENT IN THE CONTEXT OF COVID-19: APPROACHES TO ENSURING ECONOMIC SECURITY ON THE EXAMPLE OF UZBEKISTAN - RasulevAlisherFayziyevich,; ТashmatovShukhratKhamrayevich,; VoroninAlexandrovich, Sergey; BegmatovaShakhnozaAdkhamovna, (The journal of contemporary issues in business and government, 2021)
. The article discusses methodological approaches to the transition from centralized system to market relations. Strengths and weaknesses of the market mechanism have been identified. The priorities of the development of the economy of Uzbekistan and the tendencies of institutional transformations are considered. Proposals have been developed for the reform of economic management in the context of the spread of COVID-19 and the need to improve economic security.